CT Scan Value Of Temporal Bone In Assessment Of Congenital Deafness - ghayad, Haidar A.; Badr, Hani M.; Al-Hili, Mohammed (Journal of the Faculty of Medicine Baghdad, 2012)
Background:. Computed tomography (CT) of the temporal bone is the first-line recommended imaging modality for SNHL. Because it can identify inner ear malformations that may be responsible for hearing impairment. Objectives: To demonstrate CT abnormalities encountered in children with congenital deafness and to assess the value of CT in the prediction for cochlear implantation. Also to evaluate the incidence and types of inner ear abnormalities in children with congenital deafness identified with CT scan for implantation difficulties. Patients & Methods: This is a cross sectional study carried out during the period from October 2009 to October 2010 at Baghdad medical city complex on children patients who are suffering from congenital deafness. The study included 60 patients (120 ears), 27 males and 33 females, were evaluated by CT scan of temporal bone before cochlear implants. Results: Most of the cases undergo CT scan examination were normal (80%). Enlargement of the vestibular aqueduct is most common (10% ) causes of congenital inner ear malformations, followed by cochlear malformation (8.3%) while dysplasia of lateral semicircular canal found in (3.3%) of cases. Conclusion: High resolution CT scan is recommended in all patient for pre implant analysis of temporal bone morphology due to its reliability and easy availability. CT scan is the modality provided critical information on abnormalities of the otic capsule, pneumatisation of the mastoid, middle ear abnormalities, cochlear ducts patency and vascular abnormalities- thus helping to assess the suitability of the ear for implantation, determine the side to be implanted and to find any associated abnormality which could adversely influence the surgery or post operative period.